The woman's body as a residence in Habite-me (Móin-Móin Magazine - Studies in the Art of Puppetry, 2020)
This article is the result of dialogue and interaction with Carolina Garcia, actress andproducer of the theatre play Habite-me (2019). The show, defined as theater of masks, danceand puppets, has a prologue and three parts, and deals with existential themes, such as life anddeath, the relationship with the passage of time and care for others. The proposal, by enliveningthese themes and intertwining them with a woman's body, also engages in a dialogue with theother elements of the scene, acquiring different contours and expanding them. Habite-me is theresult of an exchange between artists from Brazil, Canada (Cie.Territoire 80) and Belgium.